Family difficulties in caring for patients with mental disorders: a report of experience - Tayana de Sousa Neves, Adriele Pantoja Cunha, Alice Pinheiro Moura, Lidiane da Silva Evaristo, Brenda Caroline Andrade Mileo, Érika Marcilla Sousa de Couto (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v6i3.5814